Mesenchymal stem cell-derived exosomes containing miR-145-5p reduce inflammation in spinal cord injury by regulating the TLR4/NF-κB signaling pathway - Jiang, Zhensong; Zhang, Jianru (Cell cycle (Georgetown, Tex.), 2021)
EXs (Exosomes) secreted by mesenchymal stem cells (MSCs) have the potential to treat spinal cord injury (SCI), this study aimed to further explore the therapeutic effect of EXs on SCI. Firstly, EXs were extracted from MSCs and analyzed with a transmission electron microscope. Next, MSCs with or without the miR-145-5p plasmid were injected into the SCI rat model, and then rat damage was evaluated by BBB score, HE staining and Nissl staining. And then Luciferase experiment verified the targeting relationship between miR-145-5p and TLR4. Furthermore, LPS-induced PC12 cells were established and incubated with Dil-labeled MSC-EXs to explore their effects on cell viability, apoptosis and inflammation through MTT, flow cytometry and ELISA, respectively. In addition, expressions of TLR4/NF-κB signaling pathway related factors were measured by qRT-PCR and Western blot. The results showed that after MSCs were successfully isolated, the existence of EXs in MSCs was confirmed. Moreover, MSC-EXs containing miR-145-5p improved functional recovery and reduced histopathological injury and inflammation in SCI rats. And MSC-EXs promoted miR-145-5p expression in spinal cord tissue and inhibited TLR4/NF-κB pathway activation in SCI rats. MSC-EXs inhibited LPS-induced inflammatory response and activation of the TLR4/NF-κB pathway in PC12 cells. In addition, we also found that miR-145-5p specifically targeted TLR4. TLR4 overexpression significantly reversed the effect of EX-miR-145-5p on maintaining PC12 cell viability, inhibiting apoptosis and inflammatory response, and activating TLR4/NF- κB pathway. In conclusion, mesenchymal stem cell-derived EXs containing miR-145-5p reduce inflammation in spinal cord injury by regulating the TLR4/NF-κB signaling pathway.